High-sulfur-content sulfur / linear carbon positive electrode material and application thereof
By using high sulfur content sulfur/linear carbon positive electrode material in lithium sulfur batteries, using ball mill mixing technology and the conductivity of linear carbon, the problems of poor conductivity and shuttle effect of lithium sulfur batteries under high sulfur content are solved, and high energy density and excellent cycling stability are achieved.
Patent Information
- Application Number
- CN202411959466.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
Under the high sulfur content, lithium sulfur batteries have problems such as poor conductivity, easy lithium polysulfide and shuttle effect, which affect their cycle stability and energy density.
The sulfur/linear carbon positive electrode material with high sulfur content is used to increase the proportion of sulfur through ball mill mixing technology, and the conductive properties and physical adsorption capabilities of linear carbon are used to form an efficient conductive network to suppress the shuttle effect.
Lithium sulfur batteries with high sulfur proportion have excellent discharge capacity, rate performance and cycle stability, which improves the energy density and practical application value of the battery.
Smart Images

Figure CN119812259A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium-sulfur batteries, and in particular to a sulfur / linear carbon positive electrode material with a high sulfur content and application thereof. Background Art
[0002] As a new type of secondary battery, the working principle of lithium-sulfur battery relies on the electrochemical reaction between sulfur and lithium ions. During the discharge process, the sulfur positive electrode undergoes a series of complex chemical changes, starting with the reduction of solid sulfur, forming a polysulfide intermediate soluble in the electrolyte, and finally transforming into solid lithium sulfide (Li2S). This process is accompanied by the transfer of electrons, providing the required electrical energy for the external circuit. Lithium-sulfur batteries are known for their high energy density, low cost and environmental protection characteristics. Its theoretical energy density is as high as 2600Wh / kg, far exceeding the lithium-ion batteries currently on the market, so it shows great application potential in many fields such as new energy vehicles and energy storage systems.
[0003] Although lithium-sulfur batteries have many advantages, they also have excellent electrochemical performance when achieving high sulfur content, and there are still some technical difficulties. For example, the conductivity of sulfur and its discharge product lithium sulfide is poor, which is not conducive to the high-rate charge and discharge performance of the battery; the intermediate product lithium polysulfide of lithium-sulfur batteries is easily soluble in the electrolyte and migrates between the positive and negative electrodes, causing the loss of active substances and waste of electrical energy. This "shuttle effect" significantly affects the cycle stability and capacity retention of the battery. In addition, the volume of sulfur changes significantly during the charge and discharge process, which may cause damage to the battery structure and capacity attenuation, especially in the case of high sulfur content, the volume expansion problem is more serious.
[0004] A Chinese patent with publication number CN112186162A discloses a high-load, high-area capacity lithium-sulfur battery positive electrode, and its preparation method and application, comprising the following steps: sulfur, graphene, and a binder are mixed and evenly pressed into a disc, and a graphene / sulfur composite electrode material is prepared by microwave reaction, wherein the active substance sulfur accounts for 60wt.% of the positive electrode (the sulfur percentage calculation includes active substances, carbon materials, conductive agents, binders and other substances in the positive electrode), and a high energy density of the lithium-sulfur battery is achieved by thickly coating the electrode. In addition, Akhil Mammoottil Abraham et al. prepared MoS2-WS2 heterostructure materials (Akhil Mammoottil Abraham, Karsten Thiel, Mohsen Shakouri et al. "UltrahighSulfur Loading Tolerant Cathode Architecture with Extended Cycle Life forHigh Energy Density Lithium–Sulfur Batteries" Adv. Energy Mater. 2022, 12,2201494), constructed a new sulfur host matrix, integrated multifunctional compounds to enhance the adsorption-diffusion-conversion of lithium polysulfide, and achieved high sulfur loading through self-supporting electrodes, thereby improving the energy density of lithium-sulfur batteries. However, the preparation process of this self-supporting electrode material is cumbersome, cannot be prepared on a large scale, and is not easy to commercialize.
[0005] At present, most studies are to achieve high sulfur loading by thickly coating the cathode material with low sulfur content on the current collector, or by constructing a self-assembled cathode, but this will inevitably reduce the mass energy density and volume energy density of the lithium-sulfur battery. Existing studies have shown that the specific capacity, cycle life and other properties of sulfur-based cathodes will deteriorate with the increase of sulfur content. Therefore, how to simultaneously achieve a high sulfur content and a high specific capacity of active sulfur, and then improve the battery energy density, cycle life and other performance, is an urgent problem to be solved. Summary of the invention
[0006] In view of the shortcomings of the prior art, the first object of the present invention is to provide a sulfur / linear carbon positive electrode material with a high sulfur content, which has a high discharge capacity, excellent rate performance and cycle stability under the premise of a high sulfur content.
[0007] The second object of the present invention is to provide an application of a high-sulfur content sulfur / linear carbon positive electrode material, which achieves an ultra-high sulfur ratio and is beneficial to improving the electrochemical properties such as the energy density of lithium-sulfur batteries.
[0008] To achieve the above first object, the present invention provides the following technical solutions: A sulfur / linear carbon positive electrode material with a high sulfur content is prepared from the following raw materials in weight percentage: 70.0-90.0% sulfur; 8.6-20.0% linear carbon; 0.4-2.0% conductive agent; and 1.0-8.0% binder.
[0009] Furthermore, the positive electrode material is made of the following raw materials in weight percentage: sulfur 80.0%; linear carbon 16.4%; conductive agent 0.6%; binder 3.0%.
[0010] Furthermore, the preparation process of the positive electrode material includes mixing sulfur, linear carbon, a conductive agent and a binder, and grinding them in a mixer to obtain a sulfur / linear carbon positive electrode material with a high sulfur content.
[0011] Furthermore, the linear carbon is Ketjen Black ECP600JD (KB, Japan Lion).
[0012] Furthermore, the specific surface area of the linear carbon is 1100-1400m 2 / g, specific resistance is 0.3~1.0Ω·cm.
[0013] Furthermore, the conductive agent is one or a combination of conductive carbon black (Super P), single-walled carbon nanotubes (SWCNT) and acetylene black (ACET).
[0014] Furthermore, the binder is one of sodium carboxymethyl cellulose (CMC), an aqueous dispersion of acrylonitrile multipolymer (LA133 water-based binder) and polyvinylidene fluoride (PVDF).
[0015] To achieve the above second purpose, the present invention provides the following technical solutions: Application of a high sulfur content sulfur / linear carbon positive electrode material in lithium sulfur batteries.
[0016] Furthermore, the positive electrode material and the dispersion medium are mixed for 5 to 7 hours, and the sulfur loading is 1.0 to 1.5 mg / cm 2 The positive electrode sheet is coated on the surface of the aluminum current collector, and after the coating is completed, it is post-processed to obtain a positive electrode sheet; the positive electrode sheet is then punched into a circular positive electrode sheet with a diameter of 12-15 mm using a sheet punching machine; the circular positive electrode sheet is then used as a working electrode, lithium metal is used as a counter electrode, and a diaphragm and a lithium ion electrolyte are set to assemble a lithium-sulfur battery.
[0017] Furthermore, the mass ratio of the positive electrode material to the dispersion medium is 1:10-20.
[0018] Furthermore, the dispersion medium is N-methylpyrrolidone (NMP) or water.
[0019] Furthermore, the post-treatment method is vacuum drying at 60-100° C. for 10-15 hours.
[0020] Furthermore, the separator is a polypropylene film (PP) and / or a polyethylene film (PE).
[0021] Furthermore, the electrolyte in the lithium ion electrolyte is lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).
[0022] Furthermore, the solvents in the lithium ion electrolyte are ethylene glycol dimethyl ether (DME) and 1,3-dioxolane (DOL).
[0023] Furthermore, the lithium ion electrolyte also includes lithium nitrate.
[0024] Furthermore, the electrolyte concentration of the lithium ion electrolyte is 0.8-1.2 mol / L, and the lithium nitrate concentration is 1.8-2.2 wt %.
[0025] In summary, the beneficial technical effects of the present invention are: 1. The linear carbon involved in the present invention is connected by a point structure, showing a short line shape, and the specific surface area is between 1100~1400m 2 / g, the active substance sulfur does not play a major role in entering the pore structure of linear carbon. The present invention innovatively abandons the traditional heating and melting sulfur method, and instead adopts a simpler ball milling mixing technology to prepare a high-sulfur content sulfur / linear carbon positive electrode material. During the preparation process, by increasing the proportion of sulfur, the sulfur loading per unit area of the lithium-sulfur battery can be increased without using a thick electrode, thereby enhancing the energy density and practical application value of the battery; 2. Since the electronic conductivity of elemental sulfur itself is poor, the linear carbon of the present invention must have good electrical conductivity, which enables the interconnection and interweaving of carbon elements to form an efficient conductive network, which helps to improve the discharge performance and rate performance of the battery. In addition, the linear carbon has significant physical adsorption capacity for polysulfides, which can effectively inhibit the shuttle effect and accelerate the reaction kinetics of sulfur. At the same time, its high specific surface area helps to improve the transmission efficiency of lithium ions and increase the contact area with sulfur, thereby improving the utilization rate of sulfur; 3. The lithium-sulfur battery assembled with the linear carbon of the present invention has an initial discharge capacity of 1274 mAh / g at a current density of 0.05C, and an initial efficiency of up to 95.7%. At a current density of 0.5C, the discharge capacity is 872 mAh / g, and the capacity retention rate is 80% after 312 cycles, and the capacity retention rate is 62.2% after 548 cycles. The average decay rate per cycle is 0.068%. The linear carbon can be purchased directly and is suitable for sulfur positive electrode materials of high-sulfur-loaded lithium-sulfur batteries. After being assembled into button batteries, it exhibits excellent electrochemical performance, meets the needs of commercial development, and has huge market potential; 4. The present invention realizes a high-sulfur-content positive electrode (sulfur content reaches up to 90wt%) by directly increasing the proportion of active material sulfur in the positive electrode (sulfur proportion: including linear carbon, conductive agent, binder, etc.). In this way, the positive electrode sheet can be coated thinner under the premise of achieving the same sulfur loading, which is beneficial to improving the mass energy density and volume energy density of lithium-sulfur batteries, and also realizes a high specific capacity of sulfur; in addition, the linear carbon used has been industrialized; 5. The present invention discloses a method of using linear carbon as a sulfur-attached carbon-based positive electrode material for a high-sulfur content lithium-sulfur battery. Since sulfur itself has poor conductivity, a carbon-based material with excellent conductivity is needed. Linear carbon is often used as a conductive agent due to its excellent conductivity. Its carbon atoms are interconnected to form a dense conductive network, which is conducive to the migration of lithium ions and improves the utilization rate of the active substance sulfur, thereby improving the discharge capacity of the lithium-sulfur battery and achieving high-rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a SEM picture of the linear carbon of Example 1 of the present invention at a high magnification.
[0027] Figure 2 is a SEM image of the linear carbon of Example 1 of the present invention at a low magnification.
[0028] Figure 3 It is a charge and discharge curve diagram of the lithium-sulfur battery of Example 1 of the present invention.
[0029] Figure 4 This is a cycle performance diagram of the lithium-sulfur battery of Example 1 of the present invention.
[0030] Figure 5 This is a rate performance diagram of the lithium-sulfur battery of Example 1 of the present invention.
[0031] Figure 6 It is a cycle performance diagram of the lithium-sulfur battery of Comparative Example 1 of the present invention.
[0032] Figure 7 It is a cycle performance diagram of the lithium-sulfur battery of Comparative Example 2 of the present invention.
[0033] Figure 8 It is a cycle performance diagram of the lithium-sulfur battery of Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0034] In order to make the technical means, creative features, objectives and functions achieved by the present invention clearer and easier to understand, the present invention is further explained below in conjunction with the accompanying drawings and specific implementation methods.
[0035] Example 1: A sulfur / linear carbon positive electrode material with a high sulfur content disclosed in the present invention is made of the following raw materials in weight percentage: sulfur (S) 80.0%; linear carbon (KB) 16.4%; conductive agent (SWCNT) 0.6%; binder (PVDF) 3.0%.
[0036] The preparation process of the positive electrode material includes mixing sulfur, linear carbon, conductive agent and binder, grinding in a mixer to obtain the positive electrode material. The linear carbon is Ketjen Black ECP600JD (Lion, Japan), with a specific surface area of 1100~1400m 2 / g, specific resistance is 0.3~1.0Ω·cm.
[0037] Figure 1 (a)-(b) are local SEM images of the linear carbon provided in this embodiment at higher magnifications. Figure 1 It can be seen that the linear carbon is a short linear structure formed by connecting dots.
[0038] Figure 2 The linear carbon provided in this embodiment is a local SEM image at a higher magnification, Figure 2 It can be seen that the short linear structure of carbon is intertwined to form a complete conductive network.
[0039] The present invention also discloses an application of a sulfur / linear carbon positive electrode material with a high sulfur content in a lithium-sulfur battery, and the specific implementation method thereof is as follows: S1 first mixed the positive electrode material and the dispersion medium (NMP) with a mass ratio of 1:15 for 6 hours, and then 2 Coating on the surface of the aluminum current collector, and after coating, vacuum drying at 60° C. for 10 h to obtain a positive electrode sheet; then using a sheet punching machine to punch the positive electrode sheet into a circular positive electrode sheet with a diameter of 15 mm; S2 uses a circular positive electrode as the working electrode, lithium metal as the counter electrode, and is provided with a diaphragm (PP, Celgard2500) and a lithium ion electrolyte (1M LiTFSI in DME: DOL=1:1 Vol% with 2% LiNO3). A CR2032 button battery shell is used in a glove box filled with argon gas. The battery is assembled in the order of positive electrode shell, positive electrode sheet, diaphragm, and lithium metal negative electrode from bottom to top. An appropriate amount of the above electrolyte is added, the negative electrode shell is covered, and finally sealed with a sealing machine to obtain a lithium-sulfur battery.
[0040] The assembled lithium-sulfur battery was activated three times at a current density of 0.05C and once at a current density of 0.5C, and then charged and discharged at a current density of 0.25C-0.5C for cycle performance testing.
[0041] Figure 3 The charge and discharge curve of the lithium-sulfur battery assembled with the linear carbon provided in this embodiment shows that the first discharge capacity at a current density of 0.05C is 1274mAh / g, the first coulombic efficiency is 95.7%, and the discharge curves corresponding to the second and third cycles show that the discharge capacity is slightly different, showing good reversibility.
[0042] Figure 4 The cycle performance of the lithium-sulfur battery assembled with the linear carbon provided in this embodiment is shown. The assembled lithium-sulfur battery is activated three times at a current density of 0.05C, activated once at a current density of 0.5C, and then charged and discharged at a current density of 0.25C to 0.5C for cycle performance testing. As shown in the figure, at a current density of 0.5C, the first discharge capacity is 872mAh / g; at the same time, it has excellent cycle performance, with a capacity retention rate of 80% after 312 cycles, a capacity retention rate of 62.2% after 548 cycles, and an average decay rate of 0.068% per cycle.
[0043] Figure 5 The figure shows the rate performance of the lithium-sulfur battery assembled with the linear carbon provided in this embodiment. The corresponding reversible capacities at current densities of 0.1C, 0.2C, 0.5C, 1C, and 2C are 1222, 904, 826, 764, and 689 mAh / g, respectively, showing excellent rate performance.
[0044] Example 2: A sulfur / linear carbon positive electrode material with a high sulfur content disclosed in the present invention. The difference from Example 1 is that it is made of the following raw materials in weight percentage: sulfur (S) 70.0%; linear carbon (KB) 20.0%; conductive agent (SWCNT) 2.0%; binder (PVDF) 8.0%.
[0045] Example 3: A sulfur / linear carbon positive electrode material with a high sulfur content disclosed in the present invention. The difference from Example 1 is that it is made of the following raw materials in weight percentage: sulfur (S) 85.0%; linear carbon (KB) 10.5%; conductive agent (SWCNT) 0.5%; binder (PVDF) 4.0%.
[0046] Examples 4-5 are sulfur / linear carbon positive electrode materials with a high sulfur content disclosed in the present invention. The difference from Example 1 is that the conductive agents are conductive carbon black (Super P) and acetylene black (ACET), respectively.
[0047] Examples 6-7 are sulfur / linear carbon positive electrode materials with a high sulfur content disclosed in the present invention. The difference from Example 1 is that the binders are respectively sodium carboxymethyl cellulose (CMC) and an aqueous dispersion of acrylonitrile multipolymer (LA133 aqueous binder).
[0048] Comparative Example 1 is a sulfur / carbon positive electrode material with a high sulfur content disclosed in the present invention. The difference from Example 1 is that a commercial porous carbon material MRP18 (Changzhou Chuangming Super Electric Material) is used instead of linear carbon.
[0049] Figure 6 The figure shows the cycle performance of a high-sulfur lithium-sulfur battery assembled with the commercial porous carbon material provided in this comparative example as a sulfur carrier. As shown in the figure, when activated at a current density of 0.05C, the first cycle discharge capacity is 820mAh / g, and at a current density of 0.5C, the first discharge capacity is 600mAh / g; after 450 cycles, the capacity retention rate is 50%, and the coulombic efficiency decays rapidly.
[0050] Comparative Example 2: A sulfur / carbon cathode material with a high sulfur content disclosed in the present invention, which is different from Example 1 in that glucose powder is placed in a tubular furnace, heated to 800°C at 10°C / min in an Ar gas atmosphere and kept for 5 hours. After cooling to room temperature, the powder is taken out and the linear carbon is replaced with the carbon material.
[0051] Figure 7 The figure shows the cycle performance of a high-sulfur lithium-sulfur battery assembled using the carbon material obtained by carbonization of glucose as a sulfur-attached carbon base provided in this comparative example. As shown in the figure, when activated at a current density of 0.05C, the first-cycle discharge capacity is 776mAh / g, and at a current density of 0.5C, the discharge capacity is 515mAh / g; after 125 cycles, the capacity retention rate is 87%, the coulombic efficiency is extremely low, and the cycle short-circuit occurs and cannot continue.
[0052] Comparative Example 3 is a sulfur / carbon positive electrode material with a high sulfur content disclosed in the present invention. The difference from Example 1 is that multi-walled carbon nanotubes (CNTs) are used instead of the linear carbon Ketjen black (ECP600JD) described in Example 1.
[0053] Figure 8 The figure shows the cycle performance of the high sulfur ratio lithium sulfur battery assembled by using multi-walled carbon nanotubes (CNTs) as sulfur-attached carbon base provided in this comparative example. As shown in the figure, when activated at a current density of 0.05C, the first cycle discharge capacity is 914mAh / g, and at a current density of 0.5C, the first discharge capacity is 611mAh / g; after 203 cycles, the capacity retention rate is 46%, which is much lower than that of Example 1, and the cycle attenuation rate is also very high. Multi-walled carbon nanotubes and the linear carbon disclosed in the present invention have the same linear structure, but the electrochemical performance of the two is very different.
[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A high sulfur content sulfur / linear carbon positive electrode material, characterized in that: It is made of the following raw materials in weight percentage: sulfur 70.0-90.0%; linear carbon 8.6-20.0%; conductive agent 0.4-2.0%; binder 1.0-8.0%.
2. The high sulfur content sulfur / linear carbon positive electrode material according to claim 1, characterized in that: The preparation process of the sulfur / linear carbon material comprises mixing sulfur, linear carbon, a conductive agent and a binder, and grinding them in a mixer to obtain a positive electrode material.
3. The high sulfur content sulfur / linear carbon positive electrode material according to claim 1, characterized in that: The linear carbon is Ketjen Black ECP600JD.
4. The high sulfur content sulfur / linear carbon positive electrode material according to claim 3, characterized in that: The specific surface area of the linear carbon is 1100-1400m 2 / g, specific resistance is 0.3~1.0Ω·cm.
5. The high sulfur content sulfur / linear carbon positive electrode material according to claim 1, characterized in that: The conductive agent is one or a combination of conductive carbon black, single-walled carbon nanotubes and acetylene black.
6. The high sulfur content sulfur / linear carbon positive electrode material according to claim 1, characterized in that: The binder is one of sodium carboxymethyl cellulose, aqueous dispersion of acrylonitrile multi-polymer and polyvinylidene fluoride.
7. Use of a high-sulfur content sulfur / linear carbon positive electrode material according to any one of claims 1 to 6 in a lithium-sulfur battery.
8. The use of a high sulfur content sulfur / linear carbon positive electrode material according to claim 7, characterized in that: The positive electrode material and the dispersion medium are first mixed for 5 to 7 hours, and the sulfur loading is 1.0 to 1.5 mg / cm 2 The positive electrode sheet is coated on the surface of the aluminum current collector, and after the coating is completed, it is post-processed to obtain a positive electrode sheet; the positive electrode sheet is then punched into a circular positive electrode sheet with a diameter of 12-15 mm using a sheet punching machine; the circular positive electrode sheet is then used as a working electrode, lithium metal is used as a counter electrode, and a diaphragm and a lithium ion electrolyte are set to assemble a lithium-sulfur battery.
9. The use of a high sulfur content sulfur / linear carbon positive electrode material according to claim 8, characterized in that: The mass ratio of the positive electrode material to the dispersion medium is 1:10-20.
10. The use of a high sulfur content sulfur / linear carbon positive electrode material according to claim 8, characterized in that: The post-treatment method is drying at 60-100° C. for 10-15 hours.
Citation Information
Patent Citations
High-capacity and high-surface-capacity lithium-sulfur battery positive electrode as well as preparation method and application thereof
CN112186162A
High-sulfur supported lithium-sulfur battery positive electrode, preparation method of lithium-sulfur battery positive electrode, and lithium-sulfur battery
CN109346678A